Islands apart : becoming Dominican American - Méndez, Jasminne (Piñata Books, 2022)
In ten personal essays, the author explores her experiences growing up as a Dominican in the United States, where often those around her didn't understand that she could be Black and also Spanish-speaking. Her conservative parents frowned upon dating, heels, and shaving, which alienated her from her American peers. Her Dominican community's internalized anti-blackness and a desperate desire to be accepted by her White peers caused her to create an imaginary White friend named Linda who always treated her better than her White peers, who tended to use her for the things they wanted. As she grows older, a poignant speech by Maya Angelou catches her attention, and for the first time, she sees that she can forge her own future as a Dominican American.